The Role Of The Indonesian Government In The Imposition Of Tariffs For Imported & Exported Goods In The Asean Region - Faliqin, Ferdihan Bahrul Faliqin (Faculty of Law, University of Muhammadiyaha Surabaya, 2024)
This legal research examined the role of the Indonesian government, which is tasked with overseeing the implementation of the import and export tariff system in Indonesia. At this time, with the development of the international market, countries certainly need to tighten their security in order to protect their economic systems by implementing rules that regulate the course of trade, establishing cooperation, and entering into treaties or agreements that will later bind one country to another. The laws that Indonesia has implemented into domestic regulations, such as Law No. 7 of 2014, Law no. 17 of 2006, and Law no. 39 of 2007. This research discussed the impact of implementing the tariff system on Indonesia's export and import trade and current government challenges, such as the development of world globalization, the era of digitalization, and also actions that can be categorized as crimes in the trade sectors. Dumping also occurs in international trade, which can threaten local markets, prompting countries to make agreements to combat dumping practices. The research method used is a normative research method. The approaches used are the Statute Approach and the Analytical Approach, namely, research using legislation, Trade Law Concepts, and also analysis of the implications of Legal principles as a basic reference and analysis of several laws and regulations that regulate this matter.